A digestive tract perforation occluder and its preparation method

By using a composite hydrogel made of sodium alginate and acrylamide, combined with nanosilicon dioxide particles, the mechanical properties and efficiency problems of gastrointestinal perforation sealing are solved, and rapid sealing and repair in the gastrointestinal environment is achieved.

CN116262145BActive Publication Date: 2025-06-03THE SECOND AFFILIATED HOSPITAL ARMY MEDICAL UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210562201.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-12-14
Filing Date
2022-05-23
Publication Date
2025-06-03
Estimated Expiration
2042-05-23

AI Technical Summary

Technical Problem

The prior art is difficult to effectively seal gastrointestinal perforation, especially when facing the gastric acid environment, mucus secretion and mechanical force, hydrogel materials have shortcomings in mechanical properties and sealing efficiency.

Method used

A composite hydrogel made of sodium alginate and acrylamide as the gel-forming base components is used to form a hydrogel matrix with excellent mechanical properties through cross-linking reaction, and nanosilicon dioxide particles are attached to the sealing part to improve adhesion.

Benefits of technology

It achieves rapid expansion and sealing perforation in the gastrointestinal environment, has good stretching, compression and adhesion mechanical properties, can effectively support digestive tract repair, and achieve sustained release treatment through drug loads.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116262145B_ABST
    Figure CN116262145B_ABST
Patent Text Reader

Abstract

The present invention discloses a digestive tract perforation occluder and a preparation method thereof. The occluder includes a matrix, the matrix includes a columnar occlusion part, and anti-detachment parts are fixedly connected to both ends of the occlusion part respectively. In at least one direction of the cross-section, the size of the occlusion part is smaller than that of the anti-detachment part, and the matrix is made of a biodegradable hydrogel. The occluder of the present invention can quickly occlude digestive tract perforations and has the potential for clinical application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the fields of biomaterials and implantable medical devices, and particularly relates to a digestive tract perforation occluder and a preparation method thereof. Background Art

[0002] Gastrointestinal perforation is a full-thickness injury of the gastrointestinal wall, and gastric contents spill into the abdominal cavity. Even after standard repair interventions, the mortality rate of patients reaches 10%. Gastrointestinal perforation can be caused by various etiologies, including trauma, ischemia, severe peptic ulcers, tumor progression, or endoscopic surgery. If the gastrointestinal perforation is not closed in time, the leakage of intraluminal contents will cause severe abdominal pain, abdominal infection, peritonitis, and even life-threatening sepsis.

[0003] Traditional treatment methods for gastrointestinal perforation include surgery and endoscopic closure. Surgical treatment inevitably brings serious trauma and has a high risk of leakage of gastrointestinal contents. Recently, the use of clips and occluders under endoscopy to treat gastric perforation has been widely used clinically, but metal clips cannot clamp the inflamed and sclerotic tissues around the ulcer.

[0004] Hydrogels have broad prospects in the biomedical field due to their good biocompatibility, drug-loading capacity, and adjustable mechanical properties. In the field of wound repair, hydrogels show good potential. The application of hydrogels in gastrointestinal repair faces challenges, including the gastric acid environment, mucus secretion, and frequent mechanical forces from the digestive tract. The digestive tract has about 1000 movements per day, each exceeding 5 kPa, so higher mechanical properties of hydrogels are required. Recently, some studies have reported the application of hydrogels in the treatment of gastrointestinal perforation. For example, patent document CN113181427A discloses a method of delivering a photosensitive repair material containing a photoinitiator, gelatin methacrylate GelMA, and polyacrylic acid to the tissue to be repaired in the body through an instrument, and fixing it at the tissue site to be repaired in the form of a rivet as a bioprinting scaffold, thereby achieving wound repair. However, most hydrogel materials are applied to wound tissues or mucosal surfaces in a coating manner, which has a certain therapeutic effect on superficial injuries but cannot close the perforation in time. Summary of the Invention

[0005] In view of this, one of the purposes of the present invention is to provide a digestive tract perforation occluder.

[0006] The technical solution is as follows:

[0007] A digestive tract perforation occluder, characterized in that it includes a matrix, the matrix includes a columnar plugging part, both ends of the plugging part are fixedly connected with anti-disengagement parts respectively, and in at least one direction of the cross-section, the size of the plugging part is smaller than the size of the anti-disengagement part;

[0008] The matrix is made of a biodegradable hydrogel.

[0009] As a preferred technical solution, the water absorption swelling ratio of the above-mentioned hydrogel is not less than 20.

[0010] As a preferred technical solution, the tensile fracture energy of the above-mentioned hydrogel is 4000 J / m 2 ~15000 J / m 2 .

[0011] As a preferred technical solution, under the action of a load with a maximum stress of 30 kPa, after 100 compression-release cycles, the dimensional recovery rate of the above-mentioned hydrogel block in the load acting direction is more than 94%.

[0012] As a preferred technical solution, the above-mentioned hydrogel is formed by mixing two gel-forming basic components and crosslinking them respectively, wherein one of the basic components is sodium alginate or its derivative, and the other basic component is acrylamide or its derivative.

[0013] As a preferred technical solution, the above-mentioned matrix carries drugs.

[0014] As a preferred technical solution, nano-silica particles are attached to the surface of the above-mentioned plugging part.

[0015] The second object of the present invention is to provide a preparation method of a digestive tract perforation plugging device.

[0016] Its technical solution is:

[0017] A preparation method of a plugging device, the key lies in dissolving the two basic components, a crosslinking agent and an initiator in water, degassing, then adding a crosslinking accelerator, and immediately pouring the reaction solution into a mold for reaction. After the crosslinking reaction is completed, the excess crosslinking agent and catalytic substances are removed by post-treatment to obtain the hydrogel;

[0018] The cavity of the mold has the same shape as the plugging device, and the obtained hydrogel forms the matrix; or

[0019] The cavity of the mold has a different shape from the plugging device. After obtaining the hydrogel, the matrix is processed and formed.

[0020] As a preferred technical solution, the cavity of the above-mentioned mold is rectangular, the hydrogel formed by the mold is sheet-shaped, one end middle of the hydrogel is sheared to form a notch, and finally it is rolled up from the complete end of the hydrogel to the notch end to form the matrix.

[0021] As a preferred technical solution, the above-mentioned crosslinking agent is a calcium ion crosslinking agent and a crosslinking agent of acrylamide-based compounds, the initiator is a persulfate, and the crosslinking accelerator is N,N,N',N'-tetramethylethylenediamine.

[0022] As a preferred technical solution, the two basic components are sodium alginate and dimethylacrylamide respectively, and the mass ratio of the two is 1:6 to 1:15;

[0023] The cross-linking agent of the acrylamide-based compound is N,N'-cystamine bisacrylamide, and the mass ratio of N,N'-cystamine bisacrylamide to dimethylacrylamide in the reaction solution is 0.06 to 0.24%.

[0024] As a preferred technical solution, the specific process of the post-treatment is as follows: the cross-linked reaction product is soaked in a simulated gastric acid solution for a period of time to release free calcium ions, then washed in physiological saline to remove unreacted N,N'-cystamine bisacrylamide, persulfate and N,N,N',N'-tetramethylethylenediamine, and finally the surface moisture is removed. Description of the Drawings

[0025] Figure 1 FT-IR spectra of the main raw materials for preparing the hydrogel and the prepared hydrogel;

[0026] Figure 2 Test results of the solute of the hydrogel: (A) Photograph of the freeze-dried hydrogel; (B) Photograph after swelling for 24 hours; (C) Swelling curve of the hydrogel in PBS; (D) Swelling curve of the hydrogel in a simulated gastric acid solution with pH = 1;

[0027] Figure 3 Test results of the tensile and compressive properties of the hydrogel: (A) Tensile stress-strain curve; (B) Tensile fracture energy of the hydrogel with different cross-linking agent dosage ratios; (C) Thickness recovery rate of the hydrogel after 100 times of compression with a maximum stress of 30 kPa;

[0028] Figure 4 Test results of the adhesion of the hydrogel: (A) Comparison of the maximum adhesion strength of the hydrogel lap shear test using nano-silica or water as an adhesive; (B) Comparison of the maximum adhesion strength of the hydrogel-glass slide lap shear test using nano-silica or water as an adhesive; (C) Comparison of the maximum adhesion strength of the hydrogel-skin tissue lap shear test using nano-silica or water as an adhesive; (D) Comparison of the maximum adhesion strength of the hydrogel-stomach tissue lap shear test using nano-silica or water as an adhesive;

[0029] Figure 5 Test results of the cytotoxicity of the hydrogel, where the control group (C) uses normal culture medium and the experimental group (H) uses the hydrogel conditioned medium;

[0030] Figure 6Results of the hydrogel degradation test experiment: (A) Photographs of the hydrogel sheets taken at 1 week, 2 weeks, 4 weeks, and 8 weeks respectively; (B) Comparison of the sizes of the hydrogel sheets after subcutaneous implantation for different times.

[0031] Figure 7 Schematic diagram of the construction of the dumbbell-shaped hydrogel plug and evaluation of the drug release ability: (A) Process of constructing the hydrogel plug by curling the hydrogel sheet (left) and photograph of the hydrogel plug (right); (B) Drug release curves of the samples of the fluorescein sodium-loaded hydrogel plug formed by curling the hydrogel sheet with an original length of 15 cm or 5 cm; (C) Drug release curves of the samples of the vonoprazan-loaded hydrogel plug formed by curling the hydrogel sheet with an original length of 15 cm or 5 cm.

[0032] Figure 8 Experiment on the dumbbell-shaped hydrogel plug for sealing gastric perforation: (A) Photographs of the plug sealing the gastric perforation and endoscopic observation photographs at 3 days and 28 days after the operation; (B) HE staining pictures of the gastric tissue after 28 days, where the blue arrow shows the thickness of the regenerated tissue at the wound site, the light blue arrow shows the thickness of the surrounding normal tissue, and the yellow arrow shows the thickness of the mucosa at the wound site; (C) Comparison of the heights of the regenerated villi at the wound site in different hydrogel plug groups; (D) Comparison of the thicknesses of the regenerated tissues at the wound site in different hydrogel plug groups.

[0033] Figure 9 Operation pictures of using an endoscope to deliver the hydrogel plug: (A) Placing the hydrogel plug onto the gastric perforation through the endoscope; (B) Picture 5 minutes after the hydrogel plug blocked the gastric perforation. Specific implementation manners

[0034] The present invention will be further described below in conjunction with the embodiments and the drawings.

[0035] I. Experimental materials

[0036] Nanoscale silicon particles (TM-50), N,N'-cystamine bisacrylamide (CBA), and sodium alginate (SA, product number S100128) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Dimethylacrylamide and ammonium persulfate were purchased from Shanghai Macklin Biochemical Co., Ltd. Fluorescein sodium, N,N,N',N'-tetramethylethylenediamine (TEMED), cell counting kit-8 (CCK8), and calcium carbonate were purchased from Beijing Solarbio Science & Technology Co., Ltd.

[0037] II. Synthesis of the hydrogel and preparation of the plug

[0038] (I) Synthesis of the hydrogel

[0039] Example 1

[0040] The gel-forming basic components of the hybrid hydrogel are dimethylacrylamide and sodium alginate, and CBA and calcium ions are used as their cross-linking agents respectively. First, at room temperature of 25 °C, 180 mg of sodium alginate, 1.2 g of dimethylacrylamide, 19.9 mg of calcium carbonate, 2 mg of CBA, and 9.9 mg of ammonium persulfate are all dissolved in 8.26 mL of deionized water, and then degassed in nitrogen for 20 minutes. After adding 2.5 μl of cross-linking accelerator N,N,N',N'-tetramethylethylenediamine (TEMED), stir, and immediately pour the solution into a mold. The hydrogel is cured by overnight cross-linking. After demolding, it is soaked in a simulated gastric acid solution with pH = 1 for a period of time to release free calcium ions, unreacted CBA, and catalytic substances ammonium persulfate and TEMED.

[0041] In this example, the mold used is rectangular, and the mold cavity size is 0.25 mm × 80 mm × 101 mm or 1 mm × 80 mm × 101 mm. After molding, a sheet-shaped hydrogel is obtained. According to needs, flexibly adjust the soaking time of the hydrogel in the simulated gastric acid solution. For example, the hydrogel with a size of 0.25 mm × 80 mm × 101 mm is soaked in the simulated gastric acid solution for 10 seconds, and the hydrogel with a size of 1 mm × 80 mm × 101 mm is soaked in the simulated gastric acid solution for 30 seconds. After taking out, the hydrogel is washed several times in physiological saline, and finally the surface moisture is removed to obtain a hydrogel sheet.

[0042] In this example, the mass ratio of CBA to dimethylacrylamide in the reaction system is 0.15%, and the prepared hydrogel is denoted as hydrogel-M.

[0043] Example 2

[0044] The preparation method is the same as that in Example 1. The difference is that the dosage of CBA is 0.7 mg, the mass ratio of CBA to dimethylacrylamide in the reaction system is 0.06%, and the prepared hydrogel is denoted as hydrogel-L.

[0045] Example 3

[0046] The preparation method is the same as that in Example 1. The difference is that the dosage of CBA is 2.8 mg, the mass ratio of CBA to dimethylacrylamide in the reaction system is 0.24%, and the prepared hydrogel is denoted as hydrogel-H.

[0047] Example 4

[0048] The preparation method is the same as that of Example 1. The difference is that 200 mg of sodium alginate, 1.2 g of dimethylacrylamide, 22.1 mg of calcium carbonate, 2 mg of CBA, and 9.9 mg of ammonium persulfate are all dissolved in 8.26 mL of deionized water, and then degassed in nitrogen for 20 minutes. After adding 2.5 μL of the crosslinking accelerator N,N,N',N'-tetramethylethylenediamine (TEMED), stir, and immediately pour the solution into a mold.

[0049] Example 5

[0050] The preparation method is the same as that of Example 1. The difference is that 80 mg of sodium alginate, 1.2 g of dimethylacrylamide, 8.9 mg of calcium carbonate, 2 mg of CBA, and 9.9 mg of ammonium persulfate are all dissolved in 8.26 mL of deionized water, and then degassed in nitrogen for 20 minutes. After adding 2.5 μL of the crosslinking accelerator N,N,N',N'-tetramethylethylenediamine (TEMED), stir, and immediately pour the solution into a mold.

[0051] Example 6

[0052] The preparation method is the same as that of Example 1. The difference is that the mold used has a dumbbell-shaped cavity, and a dumbbell-shaped hydrogel is obtained after demolding.

[0053] Example 7

[0054] The preparation method is the same as that of Example 1. The difference is that the mold used has a cylindrical cavity, and a cylindrical hydrogel is obtained after demolding.

[0055] (II) Preparation of the occluder

[0056] Example 8

[0057] Simple hydrogel occluder: Take the 0.25-mm-thick hydrogel sheet prepared in Example 1, cut off a 5-mm-wide rectangular hydrogel at the center of one end, cut it to half of the length of the hydrogel sheet to create a notch, forming a semi-“I”-shaped shape. Starting from the complete end, curl the hydrogel sheet towards the notched end to form a dumbbell-shaped hydrogel matrix, as Figure 7 shown in A. Among them, the smaller outer diameter section in the middle of the hydrogel matrix forms the occluding part, and the larger outer diameter section forms the anti-disengagement part. The ratio of the outer diameter of the occluding part to the outer diameter of the anti-disengagement part is about 65:100. This occluder can handle perforations about 12 mm in size.

[0058] Drug-loaded hydrogel occluder: Take the 0.25 mm thick hydrogel sheet prepared in Example 1, cut it into a half "I" shape in the above-mentioned manner, and evenly spray 6.9 mg of vonoprazan (VF) dispersed in a small amount of water onto the upper surface of the hydrogel sheet after laying it flat, or evenly spray 1 mg of acidic fibroblast growth factor (AFGF) dispersed in a small amount of water onto the upper surface of the hydrogel sheet. Then, curl the hydrogel sheet from the intact end toward the notched end to form a dumbbell-shaped hydrogel matrix loaded with drugs. When used for the treatment of gastrointestinal perforation, in addition to vonoprazan, other clinical acid-suppressing drugs can also be carried; in addition to AFGF, other drugs that promote tissue repair can also be carried.

[0059] The shape of the hydrogel prepared in Example 6 can meet the blocking requirements, and thus it is directly used as the hydrogel matrix.

[0060] For the hydrogel prepared in Example 7, a dumbbell-shaped hydrogel matrix was obtained by cutting the outer wall of the middle section of the cylindrical hydrogel.

[0061] (III) Preparation of drug-loaded occluder samples

[0062] Take the hydrogel sheet obtained in Example 1 and cut them into samples with a length of 5 cm and 15 cm respectively. Spread the sample flat, spray 1 mg of sodium fluorescein (SF) dispersed in a small amount of water evenly on the upper surface of a 5 cm or 15 cm long hydrogel sheet, and spray 6.9 mg of VF dispersed in a small amount of water evenly on the upper surface of a 5 cm or 15 cm long hydrogel sheet. Roll up each hydrogel sheet from one end to the other end to obtain a cylindrical SF-loaded occluder sample and a VF-loaded occluder sample for drug release experiments. The drug-loaded occluder sample is consistent with the curling molding method of the dumbbell-shaped hydrogel matrix. Considering that the shape of the occluder is not the main factor affecting drug release, the drug-loaded occluder sample is not made into a dumbbell shape.

[0063] (IV) Characterization of hydrogel properties

[0064] (1) Fourier transform infrared spectroscopy (FT-IR) detection

[0065] The hydrogel sheet prepared in Example 1 was taken and the sample was freeze-dried in vacuum for 24 hours before testing. All samples were measured by FT-IR (Spectrum 100, PerkinElmer) with a spectral range of 4000 cm -1 Up to 650cm -1 .

[0066] like Figure 1 , FT-IR spectrum shows that the infrared absorption curve of sodium alginate (SA) is at 1620cm -1 A broad peak of COO-stretching vibration is shown near 1420 cm-1 The C-H bending vibration peak of the secondary alcohol is shown nearby. Dimethylacrylamide (DMA) shows broad frequency peaks of C=O and N-H stretching vibrations of the amide group near 1650 cm -1 and 1610 cm -1 and shows broad absorption peaks of C=O and N-H stretching vibrations of the amide group nearby, and has absorption peaks near 1420 cm -1 (C-N stretching), 1260 cm -1 (C-N stretching) and 1140 cm -1 (C-C stretching). N,N'-cystine diacrylamide (CBA) shows a broad absorption peak of C=O stretching vibration at 1652 cm -1 , shows a broad absorption peak of N-H stretching vibration at 1616 cm -1 , and shows a characteristic absorption peak of the disulfide bond at 1230 cm -1 .

[0067] By comparing the absorption spectra of the hydrogel with those of the single raw material components, the spectral characteristics of the hydrogel can be determined. In the infrared absorption spectrum of the hydrogel, the characteristic peak of C=O stretching vibration of the amide group shifts to 1613 cm -1 , and the intensities of the characteristic peaks of C-H stretching vibration (1400 cm -1 ), C-N stretching vibration (1260 cm -1 ) and C-C stretching vibration (1140 cm -1 ) decrease.

[0068] (2) Swelling property

[0069] Take the hydrogel sheets prepared in Examples 1 to 3, dry them in a freeze dryer for 24 hours, and then weigh the initial weight Wd. After soaking in PBS or simulated gastric acid solution for 3 minutes, 5 minutes, 10 minutes, 30 minutes, 1 hour, 12 hours, and 24 hours respectively, wipe off the liquid on the surface and then record the weight Ww again. The calculation method of the swelling ratio (SR) is as follows:

[0070]

[0071] After soaking in PBS, all three hydrogels swell rapidly within the first three minutes ( Figure 2 A, 2B), and the swelling rate slows down within the subsequent 24 hours. Hydrogel-M has a relatively high swelling ratio after 24 hours, SR = 34 ± 3, which is much higher than the SR of Hydrogel-L and Hydrogel-H, which are 20 ± 2 and 24 ± 2 respectively ( Figure 2C). When considering the use of the hydrogel plug for treating gastric perforation, part of the hydrogel will be exposed to gastric acid. Therefore, the swelling properties of the hydrogel were characterized in simulated gastric acid solution (pH = 1). The SR of the hydrogel in simulated gastric acid solution was smaller than that in PBS ( Figure 2 D), but the swelling rate was still above 10 after 24 hours.

[0072] (3) Mechanical properties

[0073] The extensibility and compressibility of the hydrogel were tested on a universal tensile testing machine equipped with a 100 N or 1000 N sensor. Hydrogel specimens with dimensions of 1 mm × 10 mm × 40 mm prepared in Examples 1 to 3 were stretched at a speed of 50 mm / min at room temperature, and the stress and strain were recorded.

[0074] Using the methods of Examples 1 to 3, cylindrical hydrogel specimens with a diameter of 7 mm were prepared with a mold having a cylindrical cavity. A load was applied axially, and under a pressure of up to 30 kPa, after 100 compression - release cycles, the stress - displacement curve was recorded. All experiments were repeated at least three times.

[0075] As Figure 3 shown, when Hydrogel - L, Hydrogel - M, and Hydrogel - H were stretched to break, they could be stretched to about 4 times, 5 times, and 3 times their original lengths respectively ( Figure 3 A), and their tensile stress - strain curves also proved this ( Figure 3 A). The maximum fracture energy of Hydrogel - M was 12746 ± 1457 J / m 2 , which was much higher than 8837 ± 1319 J / m of Hydrogel - L and 2 5341 ± 1082 J / m of Hydrogel - H ( 2 ( Figure 3 B). In addition, the hydrogel withstood repeated compression without fracture and deformation. After 100 - cycle compression at a maximum stress of 30 kPa (3 times the maximum peristaltic pressure of the digestive tract), Hydrogel - L, Hydrogel - M, and Hydrogel - H showed good tolerance and still maintained 95.0%, 98.0%, and 94.3% of their initial thicknesses respectively ( Figure 3 C).

[0076] (4) Lap - shear strength

[0077] Glass and the hydrogel sheet (Hydrogel - M) prepared in Example 1 were each cut into rectangles with dimensions of 5 mm × 40 mm, and the overlapping area of the adhesive was 5 mm × 5 mm.

[0078] The preparation method of a group of lap-shear specimens is as follows: Spray 20 μl of nano-silica particles (SNP) as an adhesive on the bonding area of one side surface of the hydrogel, and gently compress the hydrogel-hydrogel or hydrogel-glass as a whole at room temperature for 3 minutes to prepare lap-shear specimens.

[0079] The preparation method of another group of lap-shear specimens is as follows: Spray a small amount of water as an adhesive on the bonding area of one side surface of the hydrogel, and gently compress the hydrogel-hydrogel or hydrogel-glass as a whole at room temperature for 3 minutes to prepare lap-shear specimens.

[0080] In the hydrogel-animal tissue lap-shear test, fresh pig skin and pig stomach tissues are obtained on the second day after euthanasia, and the subcutaneous adipose tissue and food residues in the stomach are removed to complete the preparation of skin tissue and stomach tissue. Then, the skin tissue, stomach tissue, and the hydrogel sheet (hydrogel-M) prepared in Example 1 are all cut into rectangles of 5 mm × 40 mm, and the overlapping area of the adhesive is 5 mm × 5 mm.

[0081] The preparation method of a group of lap-shear specimens is as follows: Spray 20 μl of nano-silica particles (SNP) as an adhesive on the bonding area of one side surface of the skin tissue or stomach tissue, and gently compress the hydrogel-tissue as a whole at room temperature for 3 minutes to prepare lap-shear specimens.

[0082] The preparation method of another group of lap-shear specimens is as follows: Spray a small amount of water as an adhesive on the bonding area of one side surface of the skin tissue or stomach tissue, and gently compress the hydrogel-tissue as a whole at room temperature for 3 minutes to prepare lap-shear specimens.

[0083] At room temperature, use a universal tensile testing machine to test the shear adhesion strength of the lap-shear specimens at a tensile rate of 50 mm / min until the two lap bodies of the lap-shear specimens are separated from each other.

[0084] The hydrogel also has strong adhesion on various surfaces such as glass and the hydrogel itself. The adhesion strength between hydrogels using nano-silica particles (SNP) or water as an adhesive is shown in the figure. The adhesion strength of nano-silica particles as an adhesive (18 ± 3 kPa) is significantly better than that of water (6 ± 2 kPa) ( Figure 4 A). The adhesion strength between the hydrogel and the glass sheet using nano-silica particles or water is shown in the figure. The adhesion strength of nano-silica particles as an adhesive (81 ± 5 kPa) is significantly better than that of water (28 ± 10 kPa) ( Figure 4 B).

[0085] Meanwhile, the hydrogel also has good adhesion effect on tissues under the action of nano-silica: The adhesion strength between the hydrogel and skin tissues using nano-silica particles or water is shown in the figure. The adhesion strength of nano-silica particles as an adhesive (12 ± 2 kPa) is significantly better than that of water (2 kPa)( Figure 4 C); The adhesion strength between the hydrogel and gastric tissues using nano-silica particles or water is shown in the figure. The adhesion strength of nano-silica particles as an adhesive (9 ± 2 kPa) is significantly better than that of water (4 ± 1 kPa)( Figure 4 D).

[0086] (5) Biocompatibility

[0087] Mouse embryonic fibroblasts (3T3) cells (SCSP-515, Chinese Academy of Sciences Stem Cell Bank) were cultured in hydrogel conditioned medium or complete medium, and cell viability was detected using a CCK-8 cell proliferation / cytotoxicity kit. Normal complete medium is DMEM (Sigma-Aldrich) medium containing 10% fetal bovine serum (Sigma-Aldrich) and 1% penicillin / streptomycin (Sigma-Aldrich). Conditioned medium was obtained by soaking 70 mg of synthesized hydrogel in 20 mL of complete medium for 24 hours. Cells were seeded into a 96-well cell culture plate, about 8×103 cells per well. After culturing with complete medium or conditioned medium for 24 hours or 48 hours, cell viability was detected. After adding CCK-8 reagent, it was cultured in a constant temperature cell incubator at 37 °C and 5% CO 2 for 40 minutes, and then the absorbance at 450 nm was measured.

[0088] The results of cell viability tests are as Figure 5 shown. The number of 3T3 cells in normal medium on the 1st, 2nd, and 3rd days (43396 ± 3501, 90412 ± 9131, and 348266 ± 48411) was comparable to the number of cells in hydrogel conditioned medium (45117 ± 5612, 85096 ± 7593, and 316615 ± 69342, P>0.05), proving that the hydrogel has no obvious cytotoxicity.

[0089] (6) Degradability

[0090] Adult male Sprague-Dawley rats weighing 200 g - 250 g were anesthetized by intraperitoneal injection of 1% sodium pentobarbital (Sigma-Aldrich, St. Louis, MO, USA, 5 mg / 100 g body weight). Then, two skin incisions about 1.5 cm long were made on the back, and the subcutaneous tissue and skin were carefully separated. At one wound, the prepared 10 mm × 10 mm hydrogel patch was implanted subcutaneously. The rats were sacrificed at 1, 2, 4, and 8 weeks after surgery, and the hydrogel implantation specimens were removed and measured on measuring paper for their size. The degradation rate was evaluated by measuring the remaining hydrogel area.

[0091] As Figure 6 shown, obvious fragments and pores appeared on the hydrogel sheet two weeks after implantation ( Figure 6 A). The remaining area was significantly reduced after the 4th week. The remaining areas of the hydrogel sheets at the 1st week, 2nd week, 4th week, and 8th week were 257 ± 41 mm 2 , 211 ± 17 mm 2 , 151 ± 16 mm 2 and 120 ± 19 mm 2 , respectively, indicating that the hydrogel sheets gradually degraded ( Figure 6 B).

[0092] (V) Drug release performance

[0093] After immersing the SF-loaded occluder specimens in 20 mL of pure water, 100 μl of the solution was taken out each time, and absorbance detection (450 nm) was performed at 5 minutes, 10 minutes, 30 minutes, 60 minutes, 2 hours, 6 hours, 12 hours, 24 hours, and 48 hours. After immersing the VF-loaded occluder specimens in 20 mL of pure water, at 5 minutes, 10 minutes, 30 minutes, 60 minutes, 2 hours, 6 hours, 12 hours, 24 hours, and 72 hours, 100 μl of the solution was taken out each time for high-performance liquid chromatography analysis. High-performance liquid chromatography was performed under the following conditions: the injection rate was 0.3 mL / min, mobile phase A was 0.3 mol / L trisodium phosphate: methanol: acetonitrile = 72:25:15, and mobile phase B was 0.3 mol / L trisodium phosphate: acetonitrile = 30:70.

[0094] The occluder specimens formed by curling the hydrogel sheets showed the ability to load and release different substances. The concentration of sodium fluorescein (SF) released from the drug-loaded occluder specimens showed an upward trend during the 24-hour test ( Figure 7 B). At the same time, the drug release of the drug-loaded occluder specimens with more curling layers was slower. In addition, the drug-loaded occluder specimens could continuously release VF, and the drug release rate was negatively correlated with the original length of the hydrogel sheet ( Figure 7 C). This indicates that this curled hydrogel occluder specimen has certain characteristics of slow release and continuous drug release.

[0095] (VI) Animal Experiment of Occluder for Gastric Perforation Treatment

[0096] Example 8

[0097] Rabbits weighing about 2.5 kg were anesthetized, and the abdominal cavity was exposed through a midline abdominal incision to expose the stomach. Then, a 1-cm incision was made on the greater curvature side of the stomach to create an artificial perforation. The treatment was divided into three groups: simple hydrogel occluder group, VF-loaded hydrogel treatment group, and AFGF-loaded hydrogel treatment group. After dropping 35 - 45 μl of nano-silica suspension on the occluding part of the occluder, the occluder was embedded into the wound to block the perforation, then normal saline was sprayed and monitored for 5 minutes. After confirming no obvious leakage, the abdominal cavity was closed. Gastroscopy was performed on the 3rd and 28th days after the operation. After the last gastroscopy observation, the rabbits were euthanized to collect samples. The tissue at the perforation site was removed, fixed with formalin (10% solution, pH 7.0 - 7.6) for 24 hours, and subjected to histological or immunohistochemical analysis after paraffin embedding.

[0098] The hydrogel occluder could block the hole within 5 minutes to prevent any leakage ( Figure 8 A). At the scheduled time points, the wound was monitored through an endoscope ( Figure 8 A). On the 3rd day, the three hydrogel occluders were still at the wound, indicating that they firmly blocked the perforation. In the observation on the 28th day, it was difficult to see an obvious wound. During the healing process, the AFGF group showed better healing than the other two groups. To compare the recovery of the full-thickness tissue, 4 weeks after the hydrogel occluder treatment, the rabbits were sacrificed to obtain their gastric wall tissue ( Figure 8 B). Among them, the regenerated villi of the VF-loaded hydrogel treatment group (0.95 ± 0.23 mm) and the AFGF-loaded hydrogel treatment group (1.03 ± 0.12 mm) were higher than those of the control group (0.58 ± 0.10 mm) ( Figure 8 C). In addition, calculating the regeneration rate of the gastric wall tissue at the wound according to the thickness ratio of the wound gastric wall tissue to the surrounding normal gastric wall, the VF-loaded hydrogel treatment group and the AFGF-loaded hydrogel treatment group showed better gastric wall healing than the control group. The wound gastric wall tissue regeneration rates of the three groups were 90%, 95%, and 61% respectively ( Figure 8 D).

[0099] Example 9

[0100] Endoscopic delivery test: Take the simple hydrogel plug prepared in Example 8, freeze-dry it for later use. Use an electrocautery to make a perforation with a diameter of about 10 mm on the gastric wall of anesthetized mini-pigs, and use biopsy forceps to remove the redundant tissue. Then clamp one end of the plug with biopsy forceps and fix it to the front end of the endoscope. Deliver the plug to the wound site through the esophagus with the endoscope and release it to block the perforation. Sprinkle some water to swell the hydrogel, and observe the situation of the perforation site 5 minutes after the operation.

[0101] The hydrogel plug can be quickly placed at the perforation site ( Figure 9 A), and swell within 5 minutes to block the wound ( Figure 9 B), indicating that this hydrogel plug is easy to operate through an endoscope.

[0102] Those skilled in the art can easily recognize that the hydrogel plug disclosed in the present invention can be used not only for treating gastric perforations but also for perforations of other organs in the digestive tract such as the intestine.

[0103] Advantages of the present invention: (1) Provide a digestive tract perforation plug made of degradable hydrogel. Utilizing the characteristic that the volume of the hydrogel expands significantly after absorbing water, it can quickly block the perforation;

[0104] (2) The composite hydrogel prepared with sodium alginate and acrylamide as the gel-forming basic components has excellent tensile, compressive, and adhesion mechanical properties, meeting the mechanical property requirements of digestive tract repair materials. Moreover, the adhesion between hydrogel-hydrogel also ensures that the dumbbell-shaped plugs prepared in a curled molding manner maintain a dense connection between layers, contributing to maintaining its structural integrity;

[0105] (3) The composite hydrogel has good biocompatibility and can be used as a scaffold to guide the repair and regeneration of digestive tract tissues, while the composite hydrogel gradually degrades itself;

[0106] (4) The hydrogel plug carrying functional drugs can achieve the slow release of drugs, extend the drug action time, and promote the repair of perforations;

[0107] (5) The dried hydrogel plug is easy to be delivered to the perforation site through an endoscope, facilitating clinical operation.

[0108] Finally, it should be noted that the above description is only the preferred embodiment of the present invention. Those of ordinary skill in the art, under the inspiration of the present invention and without violating the purpose and claims of the present invention, can make various similar representations, and such transformations all fall within the protection scope of the present invention.

Claims

1. A digestive tract perforation occluder, characterized in that: It includes a matrix, and the matrix includes a columnar occlusion part. Anti-detachment parts are fixedly connected to both ends of the occlusion part respectively. In at least one direction of the cross-section, the size of the occlusion part is smaller than the size of the anti-detachment part; The occluder blocks the perforation by embedding into the wound; The matrix is made of a biodegradable hydrogel and is in a dumbbell shape; The water absorption expansion rate of the hydrogel is not less than 20; The forming process of the matrix is: The hydrogel is formed by a mold. The hydrogel is in a sheet shape. A rectangular hydrogel at the center of one end is cut off to create a notch, forming a semi-"I" shape. Starting from the complete end, the hydrogel sheet is curled towards the end with the notch to form a dumbbell-shaped hydrogel matrix. The smaller outer diameter section in the middle of the hydrogel matrix forms the occlusion part, and the larger outer diameter section forms the anti-detachment part; The hydrogel is formed by mixing two gel-forming basic components and cross-linking them respectively. One of the basic components is sodium alginate or its derivative, and the other basic component is acrylamide or its derivative.

2. The digestive tract perforation occluder according to claim 1, characterized in that: The tensile fracture energy of the hydrogel is 4000 J / m 2 ~15000 J / m 2 .

3. The digestive tract perforation occluder according to claim 1, characterized in that: The matrix carries drugs.

4. The digestive tract perforation occluder according to claim 3, characterized in that: Nano-silica particles are attached to the surface of the occlusion part.

5. The preparation method of the occluder as claimed in claim 1 or 3, characterized in that: Dissolve the two basic components, a cross-linking agent, and an initiator in water, degas, then add a cross-linking accelerator, and immediately pour the reaction solution into a mold for reaction. After the cross-linking reaction is completed, remove the excess cross-linking agent and catalytic substances through post-treatment to obtain the hydrogel.

6. The preparation method according to claim 5, characterized in that: The cross-linking agent is a calcium ion cross-linking agent and a cross-linking agent of acrylamide-based compounds. The initiator is a persulfate, and the cross-linking accelerator is N,N,N',N'-tetramethylethylenediamine.

7. The preparation method according to claim 6, characterized in that: The two basic components are sodium alginate and dimethylacrylamide respectively, and their mass ratio is 1:6 to 1:15; The cross-linking agent of the acrylamide-based compound is N,N'-cystamine bisacrylamide, and the mass ratio of N,N'-cystamine bisacrylamide to dimethylacrylamide in the reaction solution is 0.06% to 0.24%.

Citation Information

Patent Citations

  • In-vivo in-situ biomanufacturing method and application thereof in in-vivo tissue repair

    CN113181427A

  • Intraesophageal stent used for esophageal rupture and stomal leak plugging

    CN104095696A

  • Gel tissue plugging material and preparation method thereof, and plugging product

    CN109106974A